Enhancing the Performance of Phase Change Memory for Embedded Applications. Issue 4 (14th February 2019) - Li, Xi; Chen, Houpeng; Xie, Chenchen; Cai, Daolin; Song, Sannian; Chen, Yifeng; Lei, Yu; Zhu, Min; Song, ZhiTang
Abstract : Focusing on meeting the requirements for embedded applications of faster switching and sensing, lower‐power consumption, higher reliability, longer cycling endurance, and higher temperature retention, a lot of progress in the phase change memory (PCM) field has been made, including materials improvement, process optimization, new circuits design, and better operation algorithms. Finally, a 128 MB embedded PCM chip has been demonstrated in 40 nm node. Using carbon‐doped Ge2 Sb2 Te5 phase change material and 3 nm thick heating bottom electrode contact (BEC) with nitride coating, a resistance ratio of more than two orders of magnitude has been achieved in Reset and Set states. Combined with the parasitic matched sensing circuit, optimized ramp‐down SET pulses, adaptive pre‐read and write‐verify methods, and automatic configure and test procedures, the chip exhibits excellent data retention and endurance characteristics with minimum program time of 200 ns, and the Reset/Set resistance ratio becomes even larger after 260 °C soldering test. The estimated data retention time is 10 years at 128 °C, and in a 128 MB full integrated chip the endurance over 10 9 cycles is achieved. It is confirmed that this PCM technology is suitable for embedded applications, especially for those with crucial requirements of high access speed, high thermal stability, and cycling endurance. Abstract : This review summarizes the authors' main progress in phase change memory (PCM) technology and presents a PCM device based on carbon‐doped Ge2 Sb2 Te5 (CGST) as a 128 MB chip, demonstrating the following key properties: minimum Read/Write time of 10 ns/200 ns, over 10 11 cycles endurance of the TiN blade bottom electrode contact with nitride coating, Reset/Set ratio over two orders of magnitude, 10‐year 128 °C data retention, and over 10 9 cycles endurance of the device. It has great potential for embedded applications.